La revolución educativa.El reto de la Universidad ante la sociedad del conocimiento - Fernández Liria, Carlos; Alegre Zahonero, Luis (Logos. Anales del Seminario de Metafísica, 2004)
In the context of European Convergence, it has non-stop been encouraged a revolution in higher education in order to face up to challenges thrown down by the socalled "knowledge society". Nevertheless, as it happens in all revolutions, by means of the revolutionary legislation we risk destroying completely what we were trying to legislate on. This essay aims to attract academic circles attention to this matter so 225 LOGOS. Anales del Seminario de Metafísica ISSN: 1575-6866 Vol. 37 (2004): 225-253 Carlos Fernández Liria La revolución educativa Luis Alegre Zahonero that, at least, this disaster is not consolidated with our collaboration.